MHealth for pediatric chronic pain: state of the art and future directions. (1st November 2020) - Richardson, Patricia A.; Harrison, Lauren E.; Heathcote, Lauren C.; Rush, Gillian; Shear, Deborah; Lalloo, Chitra; Hood, Korey; Wicksell, Rikard K.; Stinson, Jennifer; Simons, Laura E.
ABSTRACT: Introduction: Chronic pain conditions are common among children and engender cascading effects across social, emotional, and behavioral domains for the child and family. Mobile health (mHealth) describes the practice of delivering healthcare via mobile devices and may be an ideal solution to increase access and reach of evidence-based behavioral health interventions. Areas covered: The aim of this narrative review is to present a state-of-the-art overview of evidence-based mHealth efforts within the field of pediatric chronic pain and consider new and promising directions for study. Given the nascent nature of the field, published mHealth interventions in all stages of development are discussed. Literature was identified through a non-systematic search in PubMed and Google Scholar, and a review of reference lists of papers that were identified as particularly relevant or foundational (within and outside of the chronic pain literature). Expert opinion: mHealth is a promising interventional modality with early evidence suggesting it is primed to enhance behavioral health delivery and patient outcomes. There are many exciting future directions to be explored including drawing inspiration from digital health technology to generate new ways of thinking about the optimal treatment of pediatric chronic pain.